Labor adaptation to climate variability in Eastern Africa - Dou, Xiaoya; Gray, Clark; Mueller, Valerie; Sheriff, Glenn (International Food Policy Research Institute, 2016)
As countries design climate change adaptation policies, it is important to understand how workers alter behavior in response to changes in temperature. Nonetheless, the impact of temperature on labor markets is poorly documented, especially in Africa. We address this gap by analyzing panel surveys of labor choices by sector, contractual arrangement, and migration status in four East African countries. Merging survey information with high-resolution climate data, we assess how workers shift employment in response to temperature anomalies. Results suggest important distinctions between rural and urban areas. In urban areas, only agricultural self-employment and migration are responsive to temperature, with participation in both activities decreasing at high extremes. Urban out-migration is used as a tool to increase incomes in “good” years rather than an adaptation mechanism during bad years. In contrast, out-migration appears to be a means of adapting to high temperatures in rural areas, especially among households with relatively little agricultural land. The combined impact of these forces suggests that a 2 standard deviation increase in temperature results in a 7 percent increase in urban unemployment and no significant impact on rural unemployment.